Meningkatkan Hasil Belajar Siswa melalui Penggunaan Alat Peraga (MEQIP) pada Pelajaran Matematika Kelas V Sekolah Dasar - Masdani Masdani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research is a classroom action research at SDN 002 Tanjung Perepat which aims to find out how to use teaching aids (MEQIP) in improving student learning outcomes in the addition of fractions in Mathematics. The subjects in this study were 5th grade students at SDN 002 Tanjung Perepat in the even semester of the 2019/2020 school year totaling 10 people consisting of 5 male students and 5 female students. The research was carried out in 2 cycles. The results showed that the use of teaching aids (MEQIP) in improving student learning outcomes in the matter of adding fractions in Mathematics. The increase in student learning outcomes can be seen from the value of classical learning completeness in cycles 1 and 2, respectively, namely 50% and 100%.